The Impact of Biostarter Em-4 and Buffalo Feces on The Quality of Biogas Created from Sugarcane Bagasse Fiber - Zoni, Muhammad Ari; Darvina, Yenni; Ratnawulan, - (PILLAR OF PHYSICS, 2024)
Energy is one of the most important needs in life. That’s because all human activities require energy to live. New breakthroughs need to be made to overcome the energy crisis, one of which is biogas by utilizing waste. Waste that can be used is sugarcane bagasse and buffalo feces, which have the potential to produce biogas. The purpose of this study was to determine the effect of a mixture of bagasse fiber and buffalo manure with the addition of EM-4 biostarter and without EM-4 biostarter that has the potential to produce biogas. Variations in the composition of AT and buffalo feces in this study were 50%SB: 50%BF, 40%SB:60%BF and 30%SB:70%BF without using the EM-4 biostarter. batch-type digester reactor type. The method used is the experimental method. The results showed that biogas production from the composition of a mixture of bagasse fiber with buffalo feces has an influence. Where the more buffalo feces added, the more gas produced. Then for the biogas production process using EM-4 biostarter and without EM-4 biostarter, it was found that the best in producing gas was using EM-4 biostarter, this was due to the function of biostarter which accelerates biogas fermentation so that the influence on biogas production was to use EM-4 biostarter